PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SAMSUNG PADA MASYARKAT BATAM - Kang, Hendra; Raymond, Raymond (SCIENTIA JOURNAL, 2021)
Smartphones today are a mandatory requirement for everyone. Because it becomes a necessity, there is a lot of demand and supply in the community, because there are many enthusiasts there are also many manufacturers of competition in the world of communication tools. This research is a descriptive quantitative study to determine whether the brand image, product quality, word of mouth, on the purchasing decision of Samsung in Batam city. The population in this study are consumers who buy Samsung. The sample used is purposive sampling with lemeshow formula which has 100 respondents and is processed with SPSS (Statistical Package for The Social Science). The partial test results show that the brand image variable is not significant to the purchase decision, while the product quality and word of mouth variables are significant to the purchase decision. And the results of simultaneous testing of Brand Image, Product Quality, Word Of Mout have a positive and significant impact on purchasing decisions.